'This is our treehouse': Investigating play through a practice architectures lens. (May 2022) - Kaukko, Mervi; Wilkinson, Jane; Haswell, Nick
This article explores a child-led project of building a treehouse through the theory of practice architectures. It draws on video data collected by 13 children wearing microcameras (GoPro) in a multicultural Australian primary school. The data was co-analysed with the children. The article illuminates how play practices emerge, diffuse, persist and/or disappear with time. This knowledge is needed to understand the different facets of free play and build enabling conditions for its unfolding.